The prospects of hydrogen transport engineering in the context of the law of the Republic of Kazakhstan and international law - Karazhan, Б.С.; Sarsembayev, М.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This scientific article is devoted to the Kazakh legal and international legal solution to the problems of the formation and development of environmentally friendly digitalized hydrogen transport engineering in the republic. The purpose of the annotated scientific research of the topic of this article is to consider from a legal perspective the formation of a fundamentally new branch of transport engineering in the economy of the republic – hydrogen mobile construction. It is this direction in Kazakhstan's transport engineering that should be based on the introduction of digital technologies, artificial intelligence mechanisms, and automated production systems, as well as industrial robots at various sites of machine-building plants in the country. To provide organizational support for the work of the machine-building industry and its factories, new Kazakhstani laws such as: "On creating conditions for the establishment of the hydrogen transport engineering industry in the republic", "On the introduction of digital technologies and industrial robots into the production process of hydrogen vehicles", "On the creation of an industry for the disposal of obsolete all cars, electric vehicles, including hydrogen vehicles." The article suggests the names of new international multilateral and bilateral conventions and agreements related to the production and export of hydrogen vehicles, marine and river hydrogen locomotives, railway hydrogen locomotives, and wide-body and long-haul hydrogen aircraft.